Filters and filtration handbook. - Sutherland, Ken, 1931- (Elsevier, 2008)
Filters are used in many industries, especially the water, sewage, oil, gas, food and beverage, and pharmaceutical industries. This new edition of a well-established title retains the aim of being a practical account of filtration equipment and its applications. The previous edition is badly out of date, and Ken Sutherland has completely revised and re-written it, changing emphasis and content wherever necessary. It remains an essential book for the engineer working in a plant situation, who requires guidance and information on what is available and whether it is suitable for the job in hand. *Practical guide to products and their applications *Wide industrial market *The plant engineer's source-book.